Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Project Based Learning (PjBL) Pada Matei Pencemaran Lingkungan Untuk Kelas X SMA: (Development of Project Based Learning (PjBL) Student Worksheets (LKPD) on Environmental Pollution Materials for Class X SMA) - Tiur Febriyanti; Nasrul Hakim (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
The development of student worksheets (LKPD) based on Project Based Learning (PjBL) on environmental pollution material is motivated by the less varied and innovative learning media used. The media used were only in the form of PowerPoint and printed books from the library, as a result, students agreed if learning media were developed in the form of Project Based Learning (PjBL) student worksheets. This study applies the R&D (Reseach and Development) development method using the ADDIE development model steps. The results of PjBL-based LKPD product validation were declared